Factors Affecting The Adoption Of Innovation And Its Economic Implications In The Beef Cattle Industry In Peninsular Malaysiafactors Affecting The Adoption Of Innovation And Its Economic Implications In The Beef Cattle Industry In Peninsular Malaysia - Farah Adila, Abdullah (2022)
Beef cattle farming in Malaysia is an essential activity in the agricultural industry. The Demand for beef in Malaysia is higher than the supply, so the local producers need to Increase productivity to fulfil the population's needs. The low self-sufficiency and high Import dependency ratios have become the primary concern as they have had the same Pattern for many years. Besides, the uncertain climate such as flood and drought have Also affected cattle productivity as well as a spike in ruminant feed prices. The limited Grassing area and high reliance on forages have also become the main constraints in Beef cattle farming. Hence, to overcome these challenges, strategies in adopting Innovation by local cattle producers are crucial. This study aims to determine factors Affecting innovation adoption among beef cattle farmers in Peninsular Malaysia and Its economic implications in beef cattle industry. Face-to-face interview using Structured questionnaires involving 233 beef cattle farmers in Kedah, Selangor, Kelantan and Johor was conducted. The major finding indicated that herd size, farmerto- Farmer extension and access to information significantly influenced the adoption of Innovation. Moreover, the adoption of innovation and the ownership of many assets Can further improve farm performance. To earn high profits in business, beef cattle Farmers need to accept the innovations introduced and be able to control their assets Well. For policy implications, the implementation of extension programs must be Suited to the needs of the farmers, besides regular meetings among farmers and Extension agents. The information access on innovation and the market linkage is also Crucial for the players.